Pengaruh Metode Fami Insyauqin Terhadap Prestasi Menghafal Al-Quran di Pondok Pesantren Ibnu Katsir Jember Tahun 2021/2022 - Marfu’ah . (Penerbit Kyai Mojo, 2022)
This research is motivated by the researcher's curiosity about the strategies or methods that have been applied at the son of Ibnu Katsir Islamic boarding school, how important is the influence of a student's memorization if they consistently apply the fami bisyauqin method. From here the title of this research was made. Is this method able to improve student achievement in memorizing the Qur'an or vice versa. This research is a correlation research with a quantitative approach. The population used in this study were students from the seventh to the tenth batch of Pondok Putra Ibnu Katsir in 2021/2022, totaling 55 students. Collecting data using questionnaires and documentation methods. The validity of the research instrument was carried out using the product moment correlation formula. Instrument reliability is calculated using Alpha Cronbac through the SPSS application. The data analysis technique used to test the hypothesis is a simple linear regression technique at a significance level of 5%. The results of the study using a simple linear regression technique obtained: the value of the correlation or relationship (R) is 0.178. From the output, the coefficient of determination (R Square) is 0.032 or equal to 3.2%, which means that there is no effect of the fami bisyauqin method on the achievement of memorizing the Qur'an at the Ibnu Katsir Putra Islamic Boarding School. Keywords : proximity, family, achievement, memorize, Al-Qur'an